2012
DOI: 10.1017/aft.2012.5
|View full text |Cite
|
Sign up to set email alerts
|

Single Session Social Work in Hospitals

Abstract: This paper reports on three complementary research studies that set out to examine the incidence and nature of single sessions in hospital social work practice. The first study was a data‐mining exercise that used statistics recorded by practitioners in nine public hospitals over a 12‐month period to establish the extent of single session work, the clinical areas in which it occurred, and the types of issues it covered. This quantitative information was enhanced with the qualitative findings of the two subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…They found the sessions they attended helpful and most were not concerned about the availability of further sessions. Similar to Gibbons and Plath's () findings, session characteristics such as the therapist providing advice and support and creating a space in which everyone's views could be heard were viewed as helpful.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…They found the sessions they attended helpful and most were not concerned about the availability of further sessions. Similar to Gibbons and Plath's () findings, session characteristics such as the therapist providing advice and support and creating a space in which everyone's views could be heard were viewed as helpful.…”
Section: Discussionsupporting
confidence: 59%
“…One of the few studies to have gathered in‐depth feedback from clients about their experience of SST is Gibbons and Plath's () examination of single session social work practice in a public hospital setting. These authors conducted interviews with 12 clients who had a single contact with a social worker and found that clients regarded it as helpful when social workers provided information, helped them navigate the hospital system and set up support services.…”
Section: Current Projectmentioning
confidence: 99%
“…To borrow a phrase from walk-in therapists Slive et al (1995), SST is well suited to the 'fast food' culture of modern elite sport. Although it is important to recognize that psychotherapy, mental health services, and sport psychology function within distinct and very different contexts, SST methods have previously been adapted and applied across a range of differing supportive and therapeutic contexts (e.g., social work, Gibbons & Plath, 2012;high school counselling, Littrell et al, 1995). Furthermore, individual athletes or teams may not have the luxury of being able to employ a full-time sport psychologist and single session strategies may therefore assist practitioners who have infrequent meetings with athletes due to time or budgetary constraints (see Van Raalte, 1998).…”
Section: Discussion Implications and Future Directions For Sport Psmentioning
confidence: 99%
“…International Review of Sport and Exercise Psychology 9 International Review of Sport and Exercise Psychology 17 (Rosenbaum, 1994), family therapy centres (Campbell, 1999), child and adolescent mental health centres (Perkins, 2006), university counselling centres (Littrell, Malia, & Vanderwood, 1995), humanitarian settings (Paul & van Ommeren, 2013), and hospitals (Gibbons & Plath, 2012). International Review of Sport and Exercise Psychology 9 International Review of Sport and Exercise Psychology 17 (Rosenbaum, 1994), family therapy centres (Campbell, 1999), child and adolescent mental health centres (Perkins, 2006), university counselling centres (Littrell, Malia, & Vanderwood, 1995), humanitarian settings (Paul & van Ommeren, 2013), and hospitals (Gibbons & Plath, 2012).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Such initiatives have facilitated integration of diverse curricula and competencies (eg, communication skills, decision-making, complex emergency response) into health education. 9,38 This study adds to the existing research and practice guidance on allied health competencies by focusing specifically on health practice environments and single-session practice.…”
Section: Implications For Allied Health Educationmentioning
confidence: 99%